Supervisor Psychological Contract Management Developing an Integrated Perspective on Managing Employee Perceptions of Obligations - Petersitzke, Maida (Gabler Verlag : Imprint: Gabler Verlag, 2009)
The interest of organisations in the concept of psychological contracts is often limited. This is mainly due to the fact that research on this concept has been presented as highly complex and has not featured any tangible instruments for its application. Maida Petersitzke provides an overview of the literature on psychological contracts. She presents a four-tier framework that details how organisations can systematically manage the psychological contracts of their employees. Based on an empirical study of line managers and their subordinates, she also identifies ways in which individual line managers can foster positive psychological contracts that are associated with higher degrees of organisational citizenship behaviours and affective commitment towards the organisation.